2021
DOI: 10.3389/fncel.2021.772868
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Severity and Duration of Status Epilepticus, Medical Countermeasures, and a Disease-Modifier, Saracatinib, on Brain Regions in the Rat Diisopropylfluorophosphate Model

Abstract: Acute organophosphate (OP) toxicity poses a significant threat to both military and civilian personnel as it can lead to a variety of cholinergic symptoms including the development of status epilepticus (SE). Depending on its severity, SE can lead to a spectrum of neurological changes including neuroinflammation and neurodegeneration. In this study, we determined the impact of SE severity and duration on disease promoting parameters such as gliosis and neurodegeneration and the efficacy of a disease modifier, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 155 publications
(221 reference statements)
3
43
2
Order By: Relevance
“…We found FJB positive cells that were colocalized with NeuN as well as FJB positive cells without NeuN positive staining, as reported in our previous publication [ 70 ]. We counted both colocalized cells and FJB cells without NeuN in our assessment of neurodegeneration since NeuN was expected to downregulate in some neurons in response to stress [ 82 ].…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…We found FJB positive cells that were colocalized with NeuN as well as FJB positive cells without NeuN positive staining, as reported in our previous publication [ 70 ]. We counted both colocalized cells and FJB cells without NeuN in our assessment of neurodegeneration since NeuN was expected to downregulate in some neurons in response to stress [ 82 ].…”
Section: Resultssupporting
confidence: 90%
“…Human studies have shown some adverse effects to SAR administration, such as fatigue, nausea, diarrhea, and headaches [ 67 , 86 ]. Notably, we did not observe any side effects in this study with 20 mg/kg daily dose, unlike our previous study (using 25 mg/kg twice a day for the first three days) in the DFP model, where SAR-treated animals had increased weight loss and mortality compared to VEH-treated animals [ 70 ]. Although SAR treatment did not significantly mitigate weight loss or morbidity measures (Irwin analysis), it appears that 20 mg/kg is more tolerable in these animals.…”
Section: Discussioncontrasting
confidence: 73%
See 3 more Smart Citations